2020
DOI: 10.1155/2020/5923025
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Intensity, and Factors Associated with Urogenital Schistosomiasis among Women of Reproductive Age in Mbogwe District Council, Geita Region, Tanzania

Abstract: Background. Urogenital schistosomiasis remains a public health problem in Tanzania. Control programs mostly target school-going children ignoring other vulnerable groups like women of child bearing age. Previous evidence has shown that women of reproductive age suffer greatest morbidities in endemic areas. This study sought to determine the prevalence, intensity, and factors associated with urogenital schistosomiasis among women of reproductive age in the Mbogwe District. Methods. A population-based analytical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This aligns with the finding that women in the age group 31-47 (Fig 2 ) have a positive association with the infection. Similar findings have been described in the adult population of Madagascar [22], so as in other endemic countries [26][27][28][29], indicating that exposure to the parasite in adult life can have a critical role in the acquisition of the infection. Additionally, only the 11.4% reported to have received PZQ treatment in the past.…”
Section: Discussionsupporting
confidence: 85%
“…This aligns with the finding that women in the age group 31-47 (Fig 2 ) have a positive association with the infection. Similar findings have been described in the adult population of Madagascar [22], so as in other endemic countries [26][27][28][29], indicating that exposure to the parasite in adult life can have a critical role in the acquisition of the infection. Additionally, only the 11.4% reported to have received PZQ treatment in the past.…”
Section: Discussionsupporting
confidence: 85%
“… 17 The prevalence is also higher compared to another study conducted among women of reproductive age in Mbogwe district which is also endemic area, where they reported a prevalence of 4.5%. 29 The recorded high prevalence of UGS in this study group is due to the endemicity of the study area, ecological factors such as the presence of suitable snail hosts and warmer temperature and humidity and water contact activities as the study population were young and middle-aged men who spent most of their lives getting into repeated contact with water bodies. It can also be due to the absence of preventive chemotherapy programme targeting this group.…”
Section: Discussionmentioning
confidence: 76%
“…Literature data have shown that the burden of schistosomiasis in PSC and women of reproductive age in Africa varies from countries and also from a region to another within the same country. In Burkina, a west African country, the highest prevalence seen in women was 21.3% even if young female were included [22] why in in Tanzania, only 4.5% of prevalence for the women was reported [23]. Similar variation of the prevalence in the PSC are also observed within the continent [24][25][26].…”
Section: Discussionmentioning
confidence: 78%